Cultural history in France local debates, global perspectives - Cohen, Evelyne; Fléchet, Anaïs; Goetschel, Pascale; Martin, Laurent 1968- (Studies for the international society for cultural history, 2020)
"This volume, which gathers contributions presented at the annual conferences of l'Association pour le développement de l'histoire culturelle (ADHC), questions the subjects and boundaries of cultural history in France -- with regard to neighboring approaches such as cultural studies, media studies, and gender studies -- to elaborate a 'social history of representations.' Historians, philosophers and sociologists address a large variety of topics and methodological proposals. Definitions, objects and actors, memories and cultural transfers: this book depicts the major questions that underlie the historical debate at the beginning of the 21st century"--